Eficiência de fungos entomopatogênicos para o controle de Sitophilus oryzae L. (Coleoptera: Curculionidae) em condições de laboratório - Agostini, Thiago Trevisoli [UNESP]; Agostini, Lucas Trevisoli [UNESP]; Duarte, Rogério Teixeira [UNESP]; Volpe, Haroldo Xavier Linhares [UNESP]; Salas, Claudio [UNESP]; Polanczyk, Ricardo Antonio [UNESP] (My University, 2015)
The objective of this research was to evaluate, under laboratory conditions, the efficiency of strains of the entomopathogenic fungi Beauveria bassiana, Metarhizium anisopliae and Isaria fumosorosea to control Sitophilus oryzae . We performed bioassays with B. bassiana strains, IBCB 01, IBCB 17 e IBCB 18, and Isaria fumosorosea strain, ARSEF 7050, the commercial products of B. bassiana (Boveril®, PM) and M. anisopliae (Metarril ®, PM) and strains of B. bassiana and M. anisopliae grown in rice, cultivated by sugarcane mill. Unsexed adults of S. oryzae were immersed in a solution with 1.0 x 108 viable conidia / mL and placed in Petri dishes containing corn grains. For each strain we performed four replicates with fifteen insects each and the mortality was evaluated daily, for 15 days. Except for M. anisopliae strain obtained from sugarcane mill, the others entomopathogens tested were pathogenic to S. oryzae, however, caused low mortality, which range between 5 to 25%, with low possibility to be adopted as a control method for this insect in stored corn grains.
Efficiency of entomopathogenic fungi to the control of Sitophilus oryzae L.(Coleoptera: Curculionidae) under laboratory condictions
Keywords: Entomopathogens; Maize weevil; Microbial control; Stored grains